Effect of Some Environmental Stress Factors in Staphylococcus aureus’ Biofilm - El-dawy, Mohamed Megahed Abdelghany; Hasan, Omar M. (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research was to investigate if S.aureus work the formation of biofilms and also to evaluate the impacts of environmental factors on the formation of biofilms. It was shown that the pathogen can form biofilms, which have a negative impact on the health of the organism, leading to resistance to environmental stress factors. This study was designed by use Microtitre-plate(MP) technique for examination of biofilm formation of S.aureus and their relationship with some environmental stress factors, which were included temperature, glucose and sodium nitrate. The effects of biofilm formation were tested with Luria-Bertani broth (LB) supplement varying concentrations of glucose (0.1; 0.5;1.0;2.0;3.0)%, sodium nitrite (0.05;0.1;0.15;0.2)%, as well were incubated the medium at different temperatures (25;37;45)°C, individually. It was observed that the addition of glucose (3.0%) was affected by the ability isolates to adhere to the MP-surface. Glucose was showing a positive effect on the formation of isolates of the biofilm while sodium nitrite was negatively affected. Where the isolates were produced the least amount of biofilm at the concentration (0.2%) sodium nitrite. Interestingly, isolates were given the high rate of formation of the biofilm at high temperature 45°C, which has resulted in their classification among the moderate values in the composition of the biofilm.